Rancang bangun furnace temperatur tinggi dengan pengendali mikrokontrol ATMEGA 8535 menggunakan sumber pemanas Silicon Carbide (SiC) - Sulistyawan A; Anas M Najih; Priyono Priyono (Youngster Physics Journal, 2017)
It has been successfully designed high temperatur furnace using Silicon Carbide (SiC) as an electric furnace source which can be controlled by ATMEGA 8535. The result of thermocouple test with standard measuring device as calibrator in temperatur range 50 ° C - 500 ° C can work well, that have been indicated by the characteristics The temperatur in the thermocouple to the ADC (Analog to Digital Converter) value in the microcontroller is Y (ADC) = 2.0062 T + 4.6. In testing of the entire furnace system for various input voltages it can be shown that the higher operating voltage will increase the heating rate in the combustion chamber. In the design using 4 sources of heating SiC with the volume of combustion chamber 1.2 liters indicates the spread of heat is quite evenly and effectively.Keywords: Furnace, AVR ATMEGA 8535 Microcontroller, Silicon Carbide